Training practices of Japanese elite team and combat sport athletes during the COVID-19 pandemic: an interview study with support staff - Yamashita, Daichi; Yamazaki, Kazuya; Yamagishi, Takaki; Tsubokura, Hana; Washif, Jad Adrian; Mujika, Iñigo (Frontiers in Sports and Active Living, 2025)
BackgroundThe coronavirus disease 2019 (COVID-19) pandemic had a profound impact on the world of sports, particularly elite athletes. This study aimed to investigate how elite athletes adapted their training during the pandemic through semi-structured interviews with performance support staff from national (NT) and professional (PT) teams.MethodsThirteen Japanese support staff (NT = 9, PT = 4) provided insights into the challenges of maintaining training duration, intensity, and quality, as well as strategies adopted to navigate specific phases, including “during” and “after” the nationwide State of Emergency and “during” and “following” two-week quarantines, through semi-structured interviews.ResultsDuring the nationwide State of Emergency and subsequent quarantines, most NT and PT support staff reported that athletes had limited access to conventional training equipment and facilities, often relying on makeshift alternatives. When these options were insufficient, the support staff modified training content based on equipment availability. Moreover, many athletes voluntarily refrained from outdoor workouts to avoid negative public attention, despite no legal ban on outdoor training. Most NT and PT support staff relied on online platforms for group or personal sessions to help maintain fitness and motivation, although these methods were considered inadequate for achieving optimal outcomes. Upon returning from quarantine, support staff implemented phased return-to-play programs. For some athletes, the cancellation of competitions presented an opportunity to focus on thorough rehabilitation for chronic injuries. Furthermore, social isolation and uncertainty increased mental health concerns among athletes, emphasizing the need for greater psychological support. Elite athletes faced challenges, including limited indoor space, inadequate equipment, and lack of “domestic rivals” to optimize training performance.ConclusionOverall, the pandemic experience emphasized the importance of robust, adaptable athlete-support systems capable of modifying training under constrained conditions. These findings highlight the value of well-defined return-to-play approaches, better communication among support staff, and holistic support strategies (well-being, etc.) to enhance resilience during future disruptions.